Fabrication of highly efficient quartz crystal microbalance ammonia sensor based on Cu-BTC nanocomposites - Kobra Vazirinezhad; Fatemeh Shariatmadar Tehrani; Sedigheh Zeinali; Maryam Tohidi (Journal of Science: Advanced Materials and Devices)
Today, the measurement of ammonia gas as a corrosive and irritating gas in the environment is very crucial. Therefore, a simple and efficient method for its detection is very important. A quartz crystal microbalance (QCM) gas sensor modified with porous nanomaterials is proposed as a new device with high performance at ambient temperature. Metal-organic frameworks (MOFs), as a type of nanoporous material, have attracted great attention in the field of gas sensing due to their unique properties, such as high adsorption sites for gas molecules compared to other conventional sensing materials. In this work, nanocomposite films of Cu-BTC (MOF containing copper as a metal node and 1,3,5-benzene tricarboxylic acid as an organic linker) with different carbon nanotube (CNT) weight percentages are fabricated on a QCM for the detection of low amounts of ammonia at room temperature. The size and morphology, chemical, crystalline structure, and porosity properties of the synthesized Cu-BTC and Cu-BTC/CNT nanocomposites were examined by field emission scanning electron microscopy (FE-SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and BET techniques, respectively. All Cu-BTC/CNT nanocomposites showed a higher response and sensitivity to ammonia gas than both Cu-BTC and CNT individually. In this work, the best sensing behavior is observed in Cu-BTC/CNT10 nanocomposite, with a sensitivity of 8.18 Hz ppm−1, a limit of detection (LOD) of 1.97 ppm, and a limit of quantification (LOQ) of 6.57 ppm in exposure to ammonia vapors. This sensor exhibited good repeatability and reversibility, reasonable selectivity towards other volatile organic compounds (VOCs), and long-term stability during 7 weeks of testing.